Effects of triiodothyronine (T3) and diet on growth, survival, metamorphosis and digestive enzymes activity of snubnose pompano Trachinotus blochii Larvae - Baobao, Jomel Guadalquiver ([Miag-ao, Iloilo] University of the Philippines Visayas, 2012)
The development of snubnose pompano Trachinotusblochii larvae specifically the time of metamorphosis, growth, survival and activity patterns of digestive enzymes alkaline phosphatase, a-amylase, lipase and protease as affected by triidothyronine (T3) levels (0, 0.01 ppm) and diet types (Artemia, Artemia+artificial diet, artificial diet) was studied from 16 to 30 days after hatching (dah). Metamorphosis was significantly affected both by hormone treatment and diet types. T3 treated larvae fed with the three different diet types completed metamorphosis on 25 dah, 27 dh and 30 dah respectively. Untreated larvae fed with artificial diet only metamorphosed on 27 dah. None of the remaining untreated groups completed metamorphosis during the experiment. Metamorphic larvae exhibited characteristics similar to that of juvenile snubnose pompano such as silvery pigmentation, nearly or completely ofwhile lowest survival was noted in groups fed with artificial diet alone. The pattern of digestive enzyme activities was modulated by metabolic changes associated with metamorphosis and the nutritional condition of the larvae. Generally, the specific activity of alkaline phosphatase decreased with larval age and remained stable toward the end of the experiment. T3 larvae fed with Artemia had significantly higher alkaline phosphatase activity. Feed types significantly influenced the specific activity of a-amylase toward the end of the experiment. The activity increased and remained at relatively higher level in either treated or untreated larvae fed with combination of Artemia and artificial diet and artificial diet alone. There was an upward trend for lipase specific activity in all treatments with a peak during 30 dah. Activity in T3 treated larvae fed with different feed types were generally higher. For the specific activity of protease, a sharp increase was noted and the activity remained stable until the end of the experiment. Generally, higher activity was noted T3 treated larvae fed with artificial diet alone and untreated larvae fed different diet types while lower activity was observed in T3 larvae fed with Artemia and combination of Artemia and artificial diet.
Thesis (M. S. Fisheries-Aquaculture)--[Miagao, Iloilo] : U. P. Visayas, April 2012.